Editorial: serologic antibodies in primary sclerosing cholangitis – a tell‐tale sign of compromised gut‐liver immunity?. Issue 2 (25th December 2020) - Tornai, David; Papp, Maria
Abstract : LINKED CONTENT This article is linked to Wunschi et al and Wunsch & Milkiewicz papers. To view these articles, visit https://doi.org/10.1111/apt.16153 and https://doi.org/10.1111/apt.16211